DEVELOPMENT REVIEW OF THE BIDAR BOAT FESTIVAL AS AN EFFORT TO PRESERVE CULTURAL HERITAGE THROUGH THE PENTA-HELIX CONCEPT IN PALEMBANG CITY - Karo Karo, Pelliyezer; Aziz, Abdul (Politeknik Pariwisata NHI Bandung, 2024)
Sustainable tourism development hinges on robust collaboration among various stakeholders, and the Penta-Helix model—comprising government, business, academics, media, and community—serves as a comprehensive framework to facilitate this cooperation. This research seeks to evaluate the effectiveness of the Penta-Helix concept in the development and sustainability of the Bidar Boat Festival in Palembang City, an annual event that preserves and promotes the cultural heritage of traditional bidar boats. Initiated by the Palembang City Government, the festival not only celebrates regional heritage but also bolsters cultural tourism. Employing a literature study-based approach, this research reviews existing journals and publications to examine the extent of Penta-Helix integration within the festival's organizational framework. Findings indicate that while the application of the Penta-Helix concept has enhanced cooperation across stakeholders, further strengthening and more active participation from each element could amplify the festival’s reach and impact. Future recommendations suggest enhancing collaboration between the involved elements to foster long-term cultural preservation and ensure the festival's continued success as a hallmark of Palembang's cultural identity. By leveraging the Penta-Helix approach, this study contributes to the broader discourse on sustainable tourism and cultural heritage preservation through multi-stakeholder engagement.